APLIKASI INSEKTISIDA NABATI BERBAHAN TANAMAN RAWA UNTUK MENGENDALIKAN HAMA KEDELAI ULAT GRAYAK (Spodoptera litura) DI LAHAN RAWA PASANG SURUT - Syaiful Asikin; Melhanah Melhanah; Yuni Lestari (AgriPeat, 2021)
One type of pest that often attacks soybean plant leaves in tidal swamplands is the armyworm pest. The intensity of leaf damage due to armyworm attack in tidal swamps ranges from 30-95%, and can even lead to crop failure. In controlling pests in soybean plants in general, always rely on chemical insecticides. The use of these chemical insecticides has a negative impact on the environment. To overcome this, the control is directed towards environmentally friendly pest control by utilizing swamp plants as a botanical insecticide. The study used a randomized block design (RBD) with 3 treatments of swamp plant extracts (galam, kirinyuh, kepayang) and 3 controls, namely without control, botanical insecticide made from neem, chemical insecticide with the active ingredient kloraniliprol. The aim of this study was to obtain a swamp plant extract that could be used in controlling armyworm pests (Spodoptera litura). The results showed that the three types of swamp plants could be used as botanical insecticides in controlling armyworm pests, and has an effectiveness value above 70%. The highest effectiveness of botanical insecticides was obtained at the age of 75 DAP, namely Galam (78.29%), Kirinyuh (78.86%) and Kepayang (78.85%).